The modern Caribbean economy. - Karagiannis, Nikolaos; Mohammed, Debbie A. (Economics collection., 2017)
Caribbean economies have been faced with mounting challenges arising from the increasing pace of economic globalization. The financial crisis of 2007 further exacerbated economic instability due to high foreign debt, lack of competitiveness, declining productivity, and high unemployment and underemployment. This in turn has precipitated increasing social and environmental problems, including poverty, inequality, crime and violence, and environmental degradation, all of which require new perspectives and policy approaches for transformative change and sustainable development. In the 2-volume multidisciplinary edited book The Modern Caribbean Economy, Volume I: Alternative Perspectives and Policy Implications provides scholars and practitioners with alternative theoretical perspectives and concrete policy recommendations, while Volume II: Economic Development and Public Policy Challenges discusses economic, industrial, and social problems facing the Caribbean along with pragmatic proposals to successfully deal with these, while building local resilience and enhancing institutional strength in the region.